Analisis Yuridis Penerapan Produk Hukum Corporate Social Responsibility Dalam Pembangunan Daerah. - Saidah Siagian; Frediansyah Frediansyah; Nurdina Purnama Sari; Alimni Alimni; Ismail Ismail (UIN Fatmawati Sukarno Bengkulu, 2023)
Abstract: Corporate Social Responsibility (CSR) is the company's obligation to provide a portion of the profits to help the community around the company's area. However, have every mining company fulfilled its social obligations in accordance with the mandate or legal products related to CSR to the community? This normative legal research article uses a statutory approach to obtain prescriptions about more effective legal remedies related to the implementation of CSR in regional development. Several relatively large and national companies have indeed successfully implemented CSR programs. However, in general, the implementation of CSR by regional scale companies has not been maximally carried out and felt by the community, especially the local community where the company is located.Keywords: Corporate Social Responsibility; Regional Development.